Analysis of Multidisciplinary Teams in the Melhor em Casa Program in the Various Regions of Brazil - Caroline Rodrigues Lyra; Clarissa Fonseca Vollrath Possmoser; Theylor Faleiro Rodrigues; Daniel Vicentini de Oliveira; Daniele Fernanda Felipe (Arquivos do Mudi, 2025)
The Melhor em Casa Program provides humanized care, reducing the need for prolonged hospitalizations. However, the distribution of services is not homogeneous across Brazil, which may impact equity in access to this type of care. This study aimed to analyze the operationalization and outcomes of the Melhor em Casa program in Brazil, focusing on the quality of care, patient and family satisfaction, and the challenges healthcare professionals face in home care. A retrospective and ecological study was conducted, analyzing health data from 2011 to 2021, extracted from LocalizaSUS. The research included annual program records from all five Brazilian regions, evaluating the distribution of the Multiprofessional Home Care Teams (EMAD1, EMAD2) and the Support Team (EMAP). Descriptive statistical analysis was performed using Microsoft Excel®. The results indicated that the Southeast region leads in EMAD1 and EMAP averages, while the Northeast region stands out in EMAD2. The highest variability was also observed in the Southeast, suggesting differences in service organization and availability. The regional disparities identified in the study highlight challenges in the equitable distribution of home care services, which may be related to the unequal allocation of resources, regional peculiarities, and socioeconomic inequalities.